Expanding the phenotypic spectrum of osteogenesis imperfecta type V including heterotopic ossification of muscle origins and attachments. Issue 7 (16th May 2019) - Clewemar, Pantelis; Hailer, Nils P.; Hailer, Yasmin; Klar, Joakim; Kindmark, Andreas; Ljunggren, Östen; Stattin, Eva‐Lena
Abstract: Background: Osteogenesis imperfecta (OI) is a clinical and genetic heterogeneous group of connective tissue disorders, characterized by bone fragility and a propensity to fracture. Methods: In this report we describe the clinical phenotype of two patients, a 28‐year‐old woman and her mother (54 years old), both with a history of short stature and multiple fractures. Results: Exome sequencing revealed the recurring IFITM5 :c.‐14 C>T variant causing OI type V. Both patients had several fractures during childhood. CT‐scan and scintigraphy showed ossification of the origin and attachment of muscles and hypertrophic callus formation. Conclusion: Ossification of the origin and attachment of muscles seems to be part of the phenotype in patients with OI type V. Abstract : We describe the clinical phenotype of two patients, a 28‐year‐old woman and her mother, both with a history of short stature and multiple fractures.CT‐scan and scintigraphy showed ossification of the origin and attachment of muscles and hypertrophic callus formation. Exome sequencing revealed the recurring IFITM5: c.‐14 C>T variant causing Osteogenesis imperfecta type V